Suppressive effects of pterostilbene on human cytomegalovirus (HCMV) infection and HCMV-induced cellular senescence - Sanying Wang; Xuqiang Zhou; Xinyue He; Shushu Ma; Chuan Sun; Jing Zhang; Xiaogang Xu; Weihua Jin; Jin Yan; Ping Lin; Genxiang Mao (Virology Journal, 2022)
Abstract Background Human cytomegalovirus (HCMV), a member of the β-herpesvirus family, causes the establishment of a latent infection that persists throughout the life of the host and can be reactivated when immunity is weakened. To date, there is no vaccine to prevent HCMV infection, and clinically approved drugs target the stage of viral replication and have obvious adverse reactions. Thus, development of novel therapeutics is urgently needed. Methods In the current study, we identified a naturally occurring pterostilbene that inhibits HCMV Towne strain replication in human diploid fibroblast WI-38 cells through Western blotting, qPCR, indirect immunofluorescence assay, tissue culture infective dose assays. The time-of-addition experiment was carried out to identify the stage at which pterostilbene acted. Finally, the changes of cellular senescence biomarkers and reactive oxygen species production brought by pterostilbene supplementation were used to partly elucidate the mechanism of anti-HCMV activity. Results Our findings revealed that pterostilbene prevented lytic cytopathic changes, inhibited the expression of viral proteins, suppressed the replication of HCMV DNA, and significantly reduced the viral titre in WI-38 cells. Furthermore, our data showed that pterostilbene predominantly acted after virus cell entry and membrane fusion. The half-maximal inhibitory concentration was determined to be 1.315 μM and the selectivity index of pterostilbene was calculated as 26.73. Moreover, cell senescence induced by HCMV infection was suppressed by pterostilbene supplementation, as shown by a decline in senescence-associated β-galactosidase activity, decreased production of reactive oxygen species and reduced expression of p16, p21 and p53, which are considered biomarkers of cellular senescence. Conclusion Together, our findings identify pterostilbene as a novel anti-HCMV agent that may prove useful in the treatment of HCMV replication.